Photodynamic Therapy and Photobiomodulation in the Treatment of Osteonecrosis: A Series of Cases: Lasertherapy and osteonecrosis - da Silva Pereira, Vanessa; da Costa, Erick Ibraim Carlos; de Deus Silva, Lídia Laís; da Silva Ximenes, Iury; de Carvalho, Arthur Vieira; Mesquita, Karine Cestaro; Forte, Clarissa Pessoa Fernandes; Sousa Dantas, Thinali (Journal of Lasers in Medical Sciences, 2026)
Introduction: This study reports five cases of osteonecrosis treated with photobiomodulation and antimicrobial photodynamic therapy (aPDT). Methods: One patient had osteoradionecrosis, another had spontaneous osteonecrosis, and three had osteonecrosis associated with medication, all of which were smaller than 1cm, with or without bone sequestration. aPDT sessions used 0.01% methylene blue followed by 9 J of red light and photobiomodulation sessions ranging from 1 to 3 Joules of red or infrared light. In one of the cases observed, osteoplasty was necessary to reduce exposed bone height. Results: aPDT and photobiomodulation produced positive clinical responses, either alone or as adjuncts to minimally invasive procedures. Conclusion: aPDT associated with photobiomodulation, removal of necrotic bone tissue, bone reduction, and antibiotic therapy proved to be effective in treating osteonecrosis described in the five cases reported.